2000
DOI: 10.1209/epl/i2000-00347-0
|View full text |Cite
|
Sign up to set email alerts
|

New phase boundary and high-pressure thermoelasticity of ZnO

Abstract: The phase transition of zinc oxide from B4 (hexagonal wurtzite structure) to B1 (cubic rocksalt structure) has been studied by energy dispersive powder diffraction technique up to 11 GPa and 1273 K. Analysis of equation-of-state (PVT) data for the rocksalt phase yields precise values of the bulk modulus and its temperature derivative. The previously accepted P-T phase diagram is shown to be incorrect. It is established that the B1 phase is not recoverable. The equilibrium transition pressure of the B4-to-B1 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
84
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 15 publications
13
84
0
1
Order By: Relevance
“…The choice of P tr = 9.6 GPa based on averaging of ab initio estimations (that vary from 7.4 GPa [12] to 12.7 GPa [13]) and one randomly chosen value of the onset pressure of kinetically hindered phase transition at 300 K (that also varies from 7.5 GPa [7] to 10.0 GPa [14]). All this leads to completely wrong equilibrium P-T line in the high pressure -high temperature region, where the transition is governed by thermodynamics, and equilibrium experimental data are available [6,7].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The choice of P tr = 9.6 GPa based on averaging of ab initio estimations (that vary from 7.4 GPa [12] to 12.7 GPa [13]) and one randomly chosen value of the onset pressure of kinetically hindered phase transition at 300 K (that also varies from 7.5 GPa [7] to 10.0 GPa [14]). All this leads to completely wrong equilibrium P-T line in the high pressure -high temperature region, where the transition is governed by thermodynamics, and equilibrium experimental data are available [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it is known that wurtzite ZnO starts to transform into rs-ZnO already at pressures above 5 GPa [6][7][8]. At room temperature this transition is very sluggish due to the existence of a strong kinetic barrier, which hinders the nucleation of a new phase [8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In situ synchrotron radiation studies have shown that at room temperature the reversible transformation from wurtzite to rock salt phase in ZnO occurs at about 9 GPa [12][13][14][15][16][17]. Upon decompression down to 2 GPa, the rock salt phase reverts to the wurtzite one.…”
Section: Introductionmentioning
confidence: 99%